Limburgse School. (Antwerpen : ICC - Internationaal Cultureel Centrum, 1973)
Jans, Jos ; Withofs, Jan ; Van den Broek, Téjo ; Coolen, Rik ; Van Den Meersch, Vincent ; Sprankenis, André ; Vanlessen, Gido ; Hamelrijck, Ado ; Keil, Hélène ; Stockmans, Piet ; Mulkers, Urbain ; Duchateau, Hugo
Limburgse School, ICC (Internationaal Cultureel Centrum) Antwerpen, van 8 t/m 30 september 1973
boek
Keywords: Limburg